A Single-Site Retrospective, Nonrandomized Study of Accelerated Partial Breast Irradiation Brachytherapy for Early-Stage Breast Cancer Treatment to Evaluate Local Tumor Control, Cosmetic Outcome, and Toxicities. (October 2016) - Shah, Shalin; Holzwanger, Erik; Khwaja, Radhika; Fang, Deborah; Figueroa-Bodine, Jazmin; Iannuzzi, Christopher; Shi, Chengyu
Purpose: To evaluate the efficacy and safety of the accelerated partial breast irradiation brachytherapy with a combination of applicators at a community hospital cancer center. Methods and Materials: Between 2005 and 2009, 120 patients with early-stage breast cancer were being followed after treatment with accelerated partial breast irradiation brachytherapy using MammoSite, single or multilumen balloon, or Contura multilumen balloon. After their lumpectomy surgery, each patient was treated with Ir-192 high-dose rate unit following radiation therapy oncology group 0413 guidelines. The patients had multiple follow-ups at 6 months, 1 year, 2 years, 3 years, or more. Results: Based on the Harvard Breast Cosmesis Scale, 95.00% of patients described their cosmetic evaluation as the treated breast essentially the same as the opposite side (excellent) or minimal but identifiable effects were noticed from radiation (good). After a median follow-up of 36 months, the local recurrence rate was 1.66% and a disease-free survival is 98.3%. Forty-two patients reported 85 adverse events, which were fibrosis: 24.70%, hyperpigmentation: 20.00%, radiation skin reaction: 7.05%, seroma: 7.05%, breast pain: 7.05%, erythema: 5.88%, and other events were less than 5.00%. Of all the adverse events recorded, grade 1 to 3 events are 95.29% (n = 81), 2.35% (n = 2), and 2.35% (n = 2). There was no grade 4 or 5 events recorded. Conclusions: Our study has shown promising results for delivering radiation with MammoSite, single or multilumen balloon, or Contura multilumen balloon and has been successful in achieving local control in patients with early-stage breast cancer.